Pelatihan Business Model Canvas (BMC) Dalam Peningkatan Profitabilitas Usaha UMKM Di Kota Semarang - Sutaat Sutaat; Dyah Purwaningrum (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Widya Husada University Semarang community service aims to strengthen the ideas, creativity, and business planning of MSMEs business actors in the city of Semarang. This Canvas business model is a company process of creating value and gaining profits from the value created easily, sustainably both long-term and short-term. The business model canvas can be interpreted as a tool to help start-ups or existing business organizations map out their business design model. As well as changing a complicated business into an easy, simple business which is presented in the form of an analysis of one sheet of paper containing a nine-key strategic plan that integrates internal and external business strategies.